Purification of Transthyretin as Nutritional Biomarker of Selenium Status - Mahn-Osses, A (2012)
Transthyretin has been proposed as nutritional biomarker of selenium intake. Previous transthyretin purification methods used different procedures to isolate transthyretin either from plasma or from pathological urine of humans. In general, the procedure for purification of transthyretin is laborious and expensive, and extensive sample recycling is necessary for purification in appreciable amounts. This work proposes a new, promissory, and cheap two-step process to purify transthyretin from blood plasma, composed by a first aqueous two-phase system fractionation followed by affinity chromatography, using thyroxine-immobilized on epoxy-activated Sepharose CL-6B. The aqueous two-phase system fractionation was demonstrated to perform better than commercial immunoaffinity-based kits for albumin depletion in blood plasma samples and is an effective first step for transthyretin purification. Thyroxine affinity chromatography was designed to bind transthyretin with high affinity, and was demonstrated to be useful to purify transthyretin, but was unable to completely resolve transthyretin from thyroxine-binding globulin and serum albumin, although the relative amount of albumin was lowered in the eluates. This purification process could be used in nutritional diagnosis tools or as a first step in structural and functional studies. © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.